Cystiysticercosis as a differential diagnosis of knee pain: A rare case report - Ali Mohammed P; Jagdish Menon; D K Patro; Deep Sharma (International Journal of Medical Research and Review, 2015)
Cysticercosis is caused by larval stage of pork tapeworm(Taenia solium). There is difficulty in diagnosing cysticercosis by ultrasound alone in its early stage especially if the lesion is small.we need to adopt MRI for early diagnosis and for starting optimum treatment for the patient. We discuss about a case of cysticercosis of vastus medialis muscle who presented with knee pain in orthopedic OPD and medical treatment was given with complete resolution of infection. Case Report: A 31 years old male who presented with complaints of pain in the (L) knee for 2 weeks duration, difficulty in sitting cross legged and squatting for 1 week. He was also complaining of mild swelling on the medial aspect of the knee. On local examination, a diffuse swelling of distal thigh (medial aspect) with knee effusion was present with induration of vastus medialis muscle. On ultrasonography it was diagnosed as a small tear in the vastus medialis muscle.But MRI scan showed evidence of 1x0.8x0.5cm well defined oval cystic lesion in the deep muscular plane of vastus medialis in its distal one third with surrounding muscle edema and knee effusion. Patient was completely asymptomatic with full range of knee ROM after treatment with albendazole alone for 4 weeks..Conclusion: We should keep Intra muscular cysticercosis as a differential diagnosis for knee pain especially in endemic areas. Muscular cysticercosis with no other systemic involvement can be treated with albendazole alone. Since isolated cysticercosis is a rare entity we should always rule out other systemic involvement including central nervous system.